1998
DOI: 10.1038/32108
|View full text |Cite
|
Sign up to set email alerts
|

Two distinct populations of Kuiper-belt objects

Abstract: The discovery of the first member of the Kuiper belt 1 -a formerly hypothetical ancient reservoir of objects located beyond Neptune's orbit-started a revolution in our understanding of the outer Solar System: there is no longer a sharp edge at Pluto's orbit. About 60 Kuiper-belt objects, intermediate in size between comets and planets, are now known 2 to exist on stable circular orbits around the Sun, and no doubt many more objects await discovery. But owing to the recent discovery and intrinsic faintness of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
103
2

Year Published

1998
1998
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(117 citation statements)
references
References 12 publications
9
103
2
Order By: Relevance
“…Recent papers have been published discussing fairly large samples of TNOs; while some authors see these objects evenly spread over the whole color range (Barucci et al 2000;Boehnhardt et al 2001;Delsanti et al 2001;Davies 2000), others have reported that the TNO population is distributed into two well separated color classes: one of solar color, the other very red (Tegler & Romanishin 1998). It is intriguing that different groups obtain such different results.…”
Section: Dynamical Families and Their Inter-connectionsmentioning
confidence: 90%
See 1 more Smart Citation
“…Recent papers have been published discussing fairly large samples of TNOs; while some authors see these objects evenly spread over the whole color range (Barucci et al 2000;Boehnhardt et al 2001;Delsanti et al 2001;Davies 2000), others have reported that the TNO population is distributed into two well separated color classes: one of solar color, the other very red (Tegler & Romanishin 1998). It is intriguing that different groups obtain such different results.…”
Section: Dynamical Families and Their Inter-connectionsmentioning
confidence: 90%
“…Tegler and Romanishin have repeatedly reported that their observations lead to a classification of the objects in 2 separate groups in the color-color diagrams (Tegler & Romanishin 1998;, one being of neutral-blue colors, while the other is very red. While this bimodality appears evident to the eye on their color-color diagrams, other authors (Barucci et al 2000;Davies 2000;Delsanti et al 2001) do not confirm it: their color-color diagrams show continuous distributions.…”
Section: Distribution Bimodalitymentioning
confidence: 99%
“…This is not the first time that two spectrally distinct groups (i.e., a bimodality) are observed for relatively similar compositions among solar system small bodies. Emery et al (2011) reported the presence of two compositional groups among the Jupiter Trojans, while Tegler & Romanishin (1998) and later Peixinho et al (2012) reported the presence of two color groups among small TNOs and Centaurs.…”
Section: Compositional Analysis Of Our Meteorite and Asteroid Samplesmentioning
confidence: 99%
“…comm. ); ( j) Grundy et al (2008); (k) Perna et al (2010); (m) Peixinho et al (2004); (n) Sheppard & Jewitt (2002); (o) Belskaya et al (2003); (p) Sheppard (2007); (q) Tegler & Romanishin (1998); (r) Jewitt & Luu (1998); (s) Barucci et al (1999); (t) Tegler et al (2003); (u) Trujillo & Brown (2002); (v) Boehnhardt et al (2002); (w) Tegler (2011, priv. comm.…”
Section: Observationsmentioning
confidence: 99%